The Development of Preschool Children’s Awareness of Semantic Radicals in Chinese Characters - Li, Mengna; Chen, Suiqing; Wu, Shaomin (Frontiers in Communication, 2021)
The present study investigated the development of Chinese preschool children's awareness of semantic and phonetic radicals in Chinese characters. The two specific areas of focus were the development of preschool children’s awareness of the category consistency of the semantic radical and children’s bias toward using semantic or phonetic radicals to classify the character. A sample of 55 four-year-old children and 61 five-year-old children were randomly selected from a public preschool that did not include formal literacy education in its curriculum. Experiment 1 found that the 4- and 5-year-old children’s awareness of the category consistency of semantic radicals had not yet developed, regardless of the configuration of characters. Experiment 2 found that 4- and 5-year-old children had a strong bias toward using phonetic radicals rather than semantic radicals to classify characters, with the bias being stronger for characters of left-right configuration than for characters of top-bottom configuration. The current findings suggest that Chinese preschool children have an awareness of radicals in Chinese characters and that they give priority to the phonetic radical over the semantic radical.